Shifting from acquisitive to conservative: the effects of Phoradendron affine (Santalaceae) infection in leaf morpho-physiological traits of a Neotropical tree species - Scalon, Marina Correa; Reis, Sabrina Alves dos [UNESP]; Rossatto, Davi Rodrigo [UNESP] (Csiro Publishing, 2017)
Mistletoes are parasitic plants that penetrate the host branches through a modified root and connect to their xylem to acquire nutrients and water. Under mistletoe infection, resources that would otherwise be used by the host are stolen by the parasite. Our aim was to compare leaf morpho-physiological traits between healthy uninfected branches and mistletoe-infected branches of a Neotropical tree species (Handroanthus chrysotrichus (Mart. ex DC.) Mattos - Bignoniaceae). We also investigated differences between mistletoe and host leaf traits. Morphological (petiole length and thickness, leaf area and thickness, and specific leaf area) and physiological leaf traits (pre-dawn and midday water potential) were measured in 10 individuals infected with the mistletoe Phoradendron affine (Pohl ex DC.) Engl. & K.Krause (Santalaceae). Mistletoes showed smaller and thicker leaves with lower pre-dawn and midday water potential, suggesting that mistletoes are more profligate water users than the host. Host leaves from infected branches were scleromorphic and showed stronger water-use control (less negative water potential) than host leaves from uninfected branches. Our results indicated that leaves from infected branches shifted to a more conservative resource-use strategy as a response to a water and nutrient imbalance caused by mistletoe infection.
Keywords: hemiparasite; leaf morphology; leaf traits; leaf water potential; resource use